A study addressing the EC8-part 3 assessment procedures for existing RC structures - Xavier Romão (2010)
The structural safety assessment procedures proposed in Part 3 of Eurocode 8(EC8-3) for the case of reinforced concrete structures are addressed. The practicalevaluation of the member chord rotation demand according to EC8-3 is examined in detailalong with several alternative formulations. The need for these formulations isdemonstrated by presenting example situations where the EC8-3 proposal is difficult toapply. The effectiveness of the proposed approaches is assessed through an exampleapplication and recommendations for their practical use are defined.